(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Genetically modified foods have the potential toeliminate hunger and starvation in millions of people, especially in developingcountries because the genetic modification can produce large amounts of foodsthat are more nutritious. Large quantities are produced because geneticallymodified crops are more resistant to pests and drought. They also containgreater amounts of nutrients, such as proteins and vitamins. However, there areconcerns about the safety of genetically modified crops. The concerns are thatthey may contain allergenic substances due to introduction of new genes intocrops. Another concern is that genetic engineering often involves the use ofantibiotic-resistance genes as "selectable markers" and this couldlead to production of antibiotic-resistant bacterial strains that are resistantto available antibiotics. This would create a serious public health problem.The genetically modified crops might contain other toxic substances such asenhanced amounts of heavy metals and the crops might not be "substantiallyequivalent" in genome, proteome, and metabolism compared with unmodifiedcrops. Another concern is that genetically modified crops may be less nutritious;for example, they might contain lower amounts of phyto-estrogens, which protectagainst heart disease and cancer.